The Gender Impact of Pension Reform : A Cross-Country Analysis - James, Estelle; Edwards, Alejandra Cox; Wong, Rebecca (World Bank, Washington DC, 2014)
Pension systems may have a different impact on gender because women are less likely than men to work in formal labor markets and earn lower wages when they do. Recent multipillar pension reforms tighten the link between payroll contributions and benefits, leading critics to argue that they will hurt women. In contrast, supporters of these reforms argue that it will help women by the removal of distortions that favored men and the better targeted redistributions in the new systems. To test these conflicting claims and to analyze more generally the gender effect of alternative pension systems, the authors examine the differential impact of the new and old systems in three Latin American countries-Argentina, Chile, and Mexico. Based on household survey data, they simulate the wage and employment histories of representative men and women, the pensions they are likely to generate under the new and old rules, and the relative gains or losses of men and women because of the reform. The authors find that women do accumulate private annuities that are only 30-40 percent those of men in the new systems. But this effect is mitigated by sharp targeting of the new public pillars toward low earners, many of whom are women, and by restrictions on payouts from the private pillars, particularly joint annuity requirements. As a result of these transfers, total lifetime retirement benefits for women reach 60-80 percent those of men, and for "full career" women they equal or exceed benefits of men. Also as a result, women are the biggest gainers from the pension reform. For women who receive these transfers, female/male ratios of lifetime benefits in the new systems exceed those in the old systems in all three countries. Private intra-household transfers from husband to wife in the form of joint annuities play the largest role.